2012
DOI: 10.1155/2012/437264
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary Plasmacytoma of the Larynx: A Case Report of Subglottic Localization

Abstract: Extramedullary plasmacytoma (EMP) is a rare neoplasm of plasma cells, described in soft tissue outside the bone marrow. EMP of the larynx represents 0.04 to 0.45% of malignant tumors of the larynx. A male of 57 years old presented with hoarseness, dyspnea, and biphasic stridor of 2 months. The indirect laryngoscopy (IL) revealed severe edema of the posterior commissure and a polypoid mass in the right posterior lateral subglottic wall. A biopsy of the subglottic mass was performed by a direct laryngoscopy (DL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
4
0
4
Order By: Relevance
“…It is generally considered that treatment strategies included surgical excision, systemic chemotherapy, radiotherapy, or a combination of those. [13] Ge et al [14] suggested that surgical excision, either alone or with adjuvant radiotherapy, has been proposed and proved to be more beneficial than radiotherapy alone. Takahiro et al [15] showed that surgical excision offers better survival outcomes in the therapy of small and localized EMP of the larynx.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally considered that treatment strategies included surgical excision, systemic chemotherapy, radiotherapy, or a combination of those. [13] Ge et al [14] suggested that surgical excision, either alone or with adjuvant radiotherapy, has been proposed and proved to be more beneficial than radiotherapy alone. Takahiro et al [15] showed that surgical excision offers better survival outcomes in the therapy of small and localized EMP of the larynx.…”
Section: Discussionmentioning
confidence: 99%
“…Los PS son tumores infrecuentes de cabeza/ cuello y la mayoría corresponde a plasmocitoma extramedular de ubicación nasosinusal. La localización a nivel laríngeo es muy inusual 2 . En nuestra revisión, sólo se han encontrado 56 casos reportados como PEM a nivel laríngeo.…”
Section: Conclusiónunclassified
“…Estos tumores son infrecuentes y afectan con mayor preponderancia a varones de más de 50 años. Los principales síntomas están relacionados con el crecimiento local 2 . Los PS se clasifican en: plasmocitoma óseo solitario (POS) y plasmocitoma extramedular (PEM).…”
Section: Introductionunclassified
See 2 more Smart Citations